C - reactive protein levels in women with pregnancy induced hypertension - Ghosh, TK; Ghosh, S; Bhattacharjee, D (Bangladesh Journal of Medical Science, 2011)
Objective: The main objective of this study is to determine the level of C- reactive protein in pregnancy induced hypertension (PIH) along its relation with normal pregnant mothers and also to compare it with different grades of pregnancy. C-reactive protein and inflammation are interrelated. Another objective of this study is to find out the relationship of C- reactive protein, biochemical and hematological parameter in PIH as well as its clinical correlation. Materials and Methods: The study was conducted in the department of Gynaecology and department of Pathology in Burdwan Medical College West Bengal India after taking permission from ethical committee. 50 cases of PIH mothers and age and gestational matched 50 cases of normal control pregnant mothers and 50 normal healthy non pregnant adult women were included in this present study. CRP was estimated by turbidometric method. Serum Uric acid, SGPT, Serum Creatinine were estimated by semi auto analyzer, Serum ß HCG was estimated by ELISA technique. The total leukocytes count, absolute Neutrophils count, Platelet counts were done in hematological cell counter with correlation from peripheral direct smear and manual counting. Urine protein was detected by dipstick method. Results: Serum C- reactive protein was positively correlated with severity of in PIH. Results shows a significantly increased C-reactive protein in PIH (Mean SD 42.02 mg/L±18 .01 mg/L, P<0.001) in comparison to normal control mother (Mean SD 4.2 ±0.93 mg/L). Conclusion: Serum C-reactive protein levels can be used as marker for early diagnosis and intervention of PIH and can be reduced maternal as well as fetal morbidity and mortality. Key words: C - reactive protein, pregnancy induced hypertension. DOI: http://dx.doi.org/ 10.3329/bjms.v10i3.8358 BJMS 2011; 10(3): 159-162